(3YOI GdOGYj hfLGI GdSGYjs - (3GdCSOj, GdMdj, CHh GdYHGS, LeGd GdOjf, CMeO Hf eMeO Hf agO, J (B841(3g`s
(3ChdgG (B:s
(3GdMeO (B((3ddg(B) (3SGeY GdOYGA hcGTa GdHdGA(B... (3hHYO aEf Gddg JYGdi (B... (3hCdge GdSDGd hMK Ydjg (B... (3ahVYfG gPg GdQSGdI Ydi Pdc hSejfGgG(B...s
(3BNQgG (B:s
(3hdge SdGMG hYOI hfLGMG dcd eWdH hfLGI ef cd TOI (B... (3eG GNJda GdUHGM hGdeSGA hCYbH GdXdGe(B.s
(3ebGHdIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B1(3, U(B227s
(3GdPQjYI HQbe(B: 1491s
(3GdCYdGe(B: (3L(B1(3, U(B227s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs